Letter of the Editor - Herrera, Rafael Segundo (Cuban Journal of Agricultural Science, 2014)
From November 18th to 22th, 2013 the 23rd Meeting of the Latin American Association of Animal Production, the 4th International Congress of Tropical Animal Production, the 4th International Congress of Animal Improvement, the 6th International Symposium of Agro-ecological Cattle Rearing and 2nd Symposium of the Latin American Sheep and Goat Producers Federation (FOCAL) were held in Havana, Cuba, all gathered by one theme: for a sustainable cattle rearing and in harmony with the environment.